ANALISIS VITAMIN C PADA MINUMAN KEMASAN UNTUK MENINGKATKAN KEKEBALAH TUBUH PADA MASA PANDEMI COVID-19 - Aisyah Rusdin; Andi Fajriansi; Irwandi Rahmat (LPPM Institut Sains dan Kesehatan Bone, 2022)
Corona virus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus which causes symptoms of fever, cough and diarrhea, thereby lowering the body's immunity. One way to improve the human immune system is to consume vitamin C. Vitamin C as an antioxidant that can improve the immune system in humans. This study aims to analyze the content of vitamin C in packaged drinks, namely, Hemaviton C1000 and Fanta Orange flavor. This research method is a qualitative test by looking at the color changes that occur using Benedict's reagent and AgNO3 powder. The results of the qualitative test of vitamin C in packaged C drinks, namely Hemaviton C1000 and Fanta with Orange flavor using Benedict's reagent and AgNO3 powder, respectively, were brick red precipitate and black precipitate which indicated the presence of vitamin C.